Gender differences in resistance training self-efficacy and outcome expectancies in elite surfing athletes - Parsonage, J.; Secomb, J. L.; Sheppard, J. M.; Dowse, R. A.; Nimphius, S. (Journal of Australian Strength and Conditioning, 2018)
Resistance training is a fundamental modality in the physical preparation of elite surfing athletes, facilitating muscular force capabilities and concomitant changes in muscle structure. Despite this, there remains a physiological gender gap amongst elite surfers, with males recording greater upper- and lower-body strength. For resistance training to be effective in eliciting physiological change, an athlete`s motivation and adherence is imperative, of which self-efficacy (SE) and outcome expectancies (OE) have been identified as influencing factors. The current study aimed to investigate SE and OE towards resistance training in competitive male and female surfing athletes.